Impact of learning organization on organizational effectiveness – An applied study on Five Star hotels in Jordan – - Al-Za`areer, Ali Sudqi; Al-Damen, Rula Ali (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to identify the availability of learning organization characteristics and its impact on organizational effectiveness in five-star hotels in Amman. This study employed purposive sampling. The sampling unit included all employees in the administrative departments in the three hotels which consisted of (237) individuals. The results show the availability of learning organization characteristics in five- star hotels in a high degree, which indicates the awareness of five stars hotels management of the importance of learning organizations characteristics & the presence of a statistically significant effect of learning organization characteristics and its dimensions on organizational effectiveness. In light of these findings, the study provided a set of recommendations. Mainly: management of five-star hotels should give workers more freedom to do the work that is entrusted to them, and to give them more participation in the decision-making process, as well as paying more attention to financial incentives given to their employees in order to encourage continues learning among them.